The Representation of Monarchism and Rebellion: Power Struggles Depicted in The King (2019) Movie - Hendri Purnomo; Ana Widiyanti (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2024)
This study attempts to examine how the 2019 David Michod film